75‐3: Reducing Glare from Reflected Highlights in Mobile and Automotive Displays. Issue 1 (2nd June 2017) - Ward, Gregory; Yoo, Hyunjin; Soudi, Afsoon; Akhavan, Tara
Abstract : We present a method for determining the positions and intensities of reflections as they appear to a user on a glass display, using on a front‐camera video feed. From these predicted highlights, we modify displayed content to overcome glare and improve image appearance for mobile and automotive applications.